What kind of legislation can contribute to on-site management?: Comparative case studies on legislative developments in managing aquatic invasive alien plants in France, England, and Japan. Issue 2 (16th July 2020) - Kamigawara, Kenji; Nakai, Katsuki; Noma, Naohiko; Hieda, Shinya; Sarat, Emmanuelle; Dutartre, Alain; Renals, Trevor; Bullock, Richard; Haury, Jacques; Bottner, Benjamin; Damien, Jean-Patrice
Abstract: Legislation to control invasive alien species for nature conservation is a relatively new area. We examined: (1) whether prohibition of sale and release into the wild can stop dispersal of invasive alien aquatic plants; (2) who is responsible for managing an invaded site; (3) whether government procedure is needed to carry out management; and (4) whether herbicide use is legalized in managing invasive alien aquatic plants. We carried out case studies on the management of water primrose ( Ludwigia grandiflora ）in France, England, and Japan, which are all developed countries in the Palaearctic realm, and where it is regarded as one of the most invasive alien aquatic plants. All three countries have introduced prohibition of sale and release, but only England has clearly introduced landowner responsibility and has applied it. All three countries have effectively halted its commercial trade, but have not yet stopped its dispersion, while England has succeeded local eradication in a considerable part of detected sites and stabilized the number of actual sites. While in France and Japan many unmanaged sites remain, all detected sites are managed in England. France prohibited herbicide use near and in water systems; in Japan, officials are reluctant to use herbicide. On the contrary, England has legalized herbicide use around water systems, under strict conditions. The landowner responsibility is an important element of legislation to manage IAS, and legalization of herbicide use around water systems, in avoiding damages for other living organisms, could contribute to its local eradication.